Barriers to absorptive capacity in the Malaysian aerospace sector - Van Der, Patrick Heiden (2016)
International technology transfer and absorptive capacity play a trivial role in technological capacity building in newly industrialized countries. Despite various ambitious and visionary roadmaps, Malaysia‘s aerospace industry is still confined to basic manufacturing, maintenance, repair and overhaul and lacks substantial research and development and design activities. As absorptive capacity is a prerequisite for organizational learning, which is the basis for technological capacity building, identifying barriers to absorptive capacity is essential to explain why Malaysia is performing suboptimal in realizing technological capacity building in the aerospace realm. A questionnaire survey and in-depth one-on-one semi-structured interviews utilizing the Delphi survey method with respondents in the global, Southeast Asian and Malaysian aerospace sectors were executed. Data triangulation of the questionnaire and Delphi survey was applied. The generated data was statistically analyzed and the extracted results indicated inconsistencies in education and training and various institutional and organizational barriers as major impediments to Malaysian technological capacity building. The role of education and training for establishing sufficient levels of absorptive capacity is substantial and forms a fundamental part of a nation‘s ability to establish and cultivate absorptive capacity on a national or organization-specific level. Recommendations are provided to enhance Malaysia‘s absorptive capacity and assist the nation in the technological capacity building of its aerospace industry. This research further contributes to the extant literature on absorptive capacity by proposing a new model of necessitated absorptive capacity. The results carry significant implications for policy-makers, managers, professionals and academics in the field of international technology transfer and absorptive capacity